All You Need Is Cash: Corporate Cash Holdings and Investment after the Global Financial Crisis - Andreas Joseph; Christiane Kneer; Neeltje van Horen (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Cash holdings at the onset of a financial crisis are a key determinant of investment by SMEs not only during the crisis but also during the recovery period. Cash-rich SMEs could maintain their capital stock during the global financial crisis, while cash-poor rivals reduced theirs. This gave cash-rich SMEs a competitive advantage during the recovery, resulting in a persistent and growing investment gap. The amplification effect was present for SMEs with both volatile and stable cash holdings and was particularly pronounced for younger and smaller firms. Competition dynamics and borrowing constraints seem to drive this amplification effect.
Keywords: D22; E32; E44; G32; 330; SMEs; investment; cash holdings; financial crisis; misallocation